2014
DOI: 10.18055/finis3619
|View full text |Cite
|
Sign up to set email alerts
|

Gentrification, residential ethnicization and the social production of fragmented space in two multi-ethnic neighbourhoods of Lisbon and Bilbao

Abstract: -simultaneous trends for ethnicization and gentrification are contributing to the fragmentation of contemporary urban spaces. this is characterised by the emergence of new social and urban units that break the homogeneity of the modern city and lead to the development of new networks, territorially discontinuous, less neighbourhood centred and with a limited intersection. With Mouraria (Lisbon, Portugal) and san francisco (Bilbao, spain), two traditional and multiethnic neighbourhoods, as case-studies this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 12 publications
0
17
0
10
Order By: Relevance
“…The garden borders Mouraria-Intendente, the city's historic migrant reception district (Fonseca and McGarrigle 2013). This area is currently undergoing a state-led urban regeneration scheme, including refurbishing historic buildings for council offices, arts centres, new public squares and a major new park (Malheiros et al 2013;Tulumello 2015). The garden has since been reinstated but plots are now allocated and very strict rules set by the city council.…”
Section: Erasure and Violence In The Gardening Commonsmentioning
confidence: 99%
“…The garden borders Mouraria-Intendente, the city's historic migrant reception district (Fonseca and McGarrigle 2013). This area is currently undergoing a state-led urban regeneration scheme, including refurbishing historic buildings for council offices, arts centres, new public squares and a major new park (Malheiros et al 2013;Tulumello 2015). The garden has since been reinstated but plots are now allocated and very strict rules set by the city council.…”
Section: Erasure and Violence In The Gardening Commonsmentioning
confidence: 99%
“…25 Rent costs have reached Lisbon averages, but they are well below those of other historical neighborhoods. Malheiros, Carvalho, and Mendes (2013) portray influxes of young individuals with relatively low economic and relatively high cultural capital. Nevertheless, these changes are not connected with displacement or social polarization.…”
mentioning
confidence: 99%
“…Ley & Dobson, 2008), is not significantly faster than in Lisbon, and the total rate in 2011 is still only a third of the Lisbon average. Malheiros et al (2013) qualify the ongoing processes as "marginal gentrification," emphasizing how newcomers tend to establish relationships with individuals "holding a different educational level and, more …”
mentioning
confidence: 99%
“…In this regard, it has been noted that the residential proximity between households or groups belonging to different social classes can favour contact, but this does not necessarily reverberate in subsequent social cooperation and a positive flow of capital from the middle class to the lower class (Heringa et al, 2017). It has been observed that in urban areas with some social mix, for example, where urban renewal processes have attracted a middle class (Malheiros et al, 2013), or in areas where processes of urban decay have attracted families with fewer resources (Alves, 2017a), the symbolic and/or cultural distance associated with linguistic differences and lifestyles tends to be more important than the fact that people live nearby. This is the conclusion presented by Colomb (2007) in London where, allegedly, the mix of housing tenures, which has resulted in relative physical proximity between different socio-economic groups, does not ensure proximity in public spaces, schools, services, and shops.…”
Section: On the Effects Of Social MIXmentioning
confidence: 99%